Complementary Chinese Herbal Medicine Treatment is Associated with a Reduction of Surgical Rate in Patients with Dysfunctional Uterine Bleeding: A Propensity-Score Matched Cohort Study - Lin YR; Lin WC; Wu MY; Lin CL; Yang ST; Yen HR (Dove Medical Press, 2024)
Yi-Rong Lin,1 Wu-Chou Lin,1,2 Mei-Yao Wu,3- 5 Cheng-Li Lin,6 Su-Tso Yang,1,7,* Hung-Rong Yen1,4,5,8,* 1Graduate Institute of Chinese Medicine, School of Chinese Medicine, College of Chinese Medicine, China Medical University, Taichung, 404, Taiwan; 2Department of Obstetrics and Gynecology, China Medical University Hospital, Taichung, 404, Taiwan; 3School of Post-Baccalaureate Chinese Medicine, College of Chinese Medicine, China Medical University, Taichung, 404, Taiwan; 4Department of Chinese Medicine, China Medical University Hospital, Taichung, 404, Taiwan; 5Research Center for Traditional Chinese Medicine, Department of Medical Research, China Medical University Hospital, Taichung, 404, Taiwan; 6Management Office for Health Data, China Medical University Hospital, Taichung, 404, Taiwan; 7Department of Radiology, China Medical University Hospital, Taichung, 404, Taiwan; 8Chinese Medicine Research Center, China Medical University, Taichung, 404, Taiwan*These authors contributed equally to this workCorrespondence: Hung-Rong Yen, School of Chinese Medicine, College of Chinese Medicine, China Medical University, 91 Hsueh-Shih Road, North District, Taichung, 404328, Taiwan, Tel +886-4-22053366 ext. 3001, Fax +886-4-22365141, Email hungrongyen@mail.cmu.edu.tw Su-Tso Yang, Department of Radiology, China Medical University Hospital, 2 Yude Road, North District, Taichung, 404327, Taiwan, Tel +886-4-22052121 ext. 5470, Fax +886-4-22365141, Email yangst@mail.cmu.edu.twBackground: Many patients with dysfunctional uterine bleeding (DUB) seek traditional medicine consultations. This study intended to investigate the association of complementary Chinese herbal medicine (CHM) with the surgery rate in patients with DUB in Taiwan.Methods: We enrolled 43,027 patients with newly diagnosed DUB (ICD-9-CM codes 626.8) from the National Health Insurance Research Database in Taiwan during the period of 1997 to 2010. Among them, 38,324 were CHM users, and 4703 did not receive CHM treatment. After performing a 1:1 propensity-score match based on patients' age (per 5 years), comorbidities, conventional drugs, childbirth status, duration from the diagnosis year of DUB and index year, there were an equal number (n=4642) of patients in the CHM cohort and non-CHM cohort. The outcome measurement was the comparison of incidences of surgical events, including hysterectomy and endometrial ablation, in the two cohorts before the end of 2013.Results: CHM users had a lower incidence of surgery than non-CHM users (adjusted HR 0.27, 95% CI: 0.22- 0.33). The cumulative incidence of surgery was significantly lower in the CHM cohort during the follow-up period (Log rank test, p < 0.001). A total of 146 patients in the CHM cohort (4.99 per 1000 person-years) and 485 patients in the non-CHM cohort (20.19 per 1000 person-years) received surgery (adjusted HR 0.27, 95% CI: 0.22- 0.33). CHM also reduced the risk of surgery in DUB patients with or without comorbidities. Regardless of childbirth status or whether patients took NSAIDs, tranexamic acid or progesterone, fewer patients in the CHM cohort underwent surgery than in the non-CHM cohort. The most commonly prescribed single herb and formula were Yi-Mu-Cao (Herba Leonuri) and Jia-Wei-Xiao-Yao-San, respectively.Conclusion: The real-world data revealed that CHM is associated with a reduced surgery rate in DUB patients. This information may be provided for further clinical investigations and policy-making.Keywords: complementary and alternative medicine, Chinese herbal medicine, dysfunctional uterine bleeding, hysterectomy, National Health Insurance Research Database, surgery